2013
DOI: 10.1186/1475-2867-13-55
|View full text |Cite
|
Sign up to set email alerts
|

Marine algal natural products with anti-oxidative, anti-inflammatory, and anti-cancer properties

Abstract: For their various bioactivities, biomaterials derived from marine algae are important ingredients in many products, such as cosmetics and drugs for treating cancer and other diseases. This mini-review comprehensively compares the bioactivities and biological functions of biomaterials from red, green, brown, and blue-green algae. The anti-oxidative effects and bioactivities of several different crude extracts of algae have been evaluated both in vitro and in vivo. Natural products derived from marine algae prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
147
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(157 citation statements)
references
References 108 publications
7
147
0
3
Order By: Relevance
“…All 18 extracts exhibited a degree of inhibition of production of the inflammatory mediator NO, whereby the activity followed the order: non-polar extracts > intermediate polarity extracts > polar extracts. Non-polar (DCM) extracts are the FA-rich fraction and also known to contain phenolic compounds as well as pigments; all of which have unique functions in inflammatory metabolism (Jaswir and Monsur 2011;Lee et al 2013). Interestingly, n-3 PUFA have been reported as modulators of the activity of nitric oxide synthase (NOS) (Radosinska et al 2011), one of the primary enzymes involved in NO production.…”
Section: Discussionmentioning
confidence: 99%
“…All 18 extracts exhibited a degree of inhibition of production of the inflammatory mediator NO, whereby the activity followed the order: non-polar extracts > intermediate polarity extracts > polar extracts. Non-polar (DCM) extracts are the FA-rich fraction and also known to contain phenolic compounds as well as pigments; all of which have unique functions in inflammatory metabolism (Jaswir and Monsur 2011;Lee et al 2013). Interestingly, n-3 PUFA have been reported as modulators of the activity of nitric oxide synthase (NOS) (Radosinska et al 2011), one of the primary enzymes involved in NO production.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that not only medical plants, but also algae contain beneficial non-nutritive agents such as polyphenols, chlorophylls, and sulfated polysaccharides, which possess antimutagenicity, anticarcinogenicity, and antioxidant activity (Cornish and Garbary, 2010;Lee et al, 2013). We previously demonstrated that the amounts of total phenolic compounds, total carbohydrates, and sulfates of the hot water extract were greater than those of raw materials (Thumvijit et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Avoiding exposure to either carcinogens or other risk factors can prevent cancer. Moreover, there are numerous reports of naturally occurring substances that inhibit cancer formation; sources of these substances include plants, animals, and microorganisms such as algae (Nobili et al, 2009;Lee et al, 2013;Muthuirulappan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[57]. Another species Sargassum wightii exhibited anti inflammatory effects [58]. Alcoholic extract of S. ilicifilium was tested against five human cancer cell line MCF-7, MDA-MB-231, HeLa, HepG2, HT-29 and the extract shows an anti proliferative effect against all the five cancer cell line in a dose regulated fashion [59].…”
Section: Sargassummentioning
confidence: 99%
“…Dalton's Ascitic lymphoma, HepG2, HT-29, Ca co-2, T47D, MDA-MB468 and /NIH 313, [55][56][57][58][59][60] Stypopodium sp SH-SY5Y, RBL-2H3, (Raw267), (V79), Caco-2. DU-145 [53,62] Undaria sp is one of the important genera under Pheophyceae.…”
Section: Solieriamentioning
confidence: 99%